2003
DOI: 10.1128/aem.69.9.5207-5211.2003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cry1I- Type Genes from Bacillus thuringiensis Strains and Characterization of a Novel cry1I- Type Gene

Abstract: A PCR-restriction fragment length polymorphism method for identification of cry1I-type genes from Bacillus thuringiensis was established by designing a pair of universal primers based on the conserved regions of the genes to amplify 1,548-bp cry1I-type gene fragments. Amplification products were digested with the Bsp119I and BanI enzymes, and four kinds of known cry1I-type genes were successfully identified. The results showed that cry1I-type genes appeared in 95 of 115 B. thuringiensis isolates and 7 of 13 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 26 publications
2
95
1
Order By: Relevance
“…2B), which suggests that these strains may be promising Bt resource for the controlling of pests. Specially, we detected the insecticidal crystal protein genes harbored in strain JF19-2 by using all the primers based on the conserved regions of each class of cry and cyt genes as previously described by Sauka et al (19) and Su (22). But only one PCR product about 1.5 kb was obtained using the primers II (+)/II (-) (data not shown), which revealed that this strain may contain only one cry2 gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2B), which suggests that these strains may be promising Bt resource for the controlling of pests. Specially, we detected the insecticidal crystal protein genes harbored in strain JF19-2 by using all the primers based on the conserved regions of each class of cry and cyt genes as previously described by Sauka et al (19) and Su (22). But only one PCR product about 1.5 kb was obtained using the primers II (+)/II (-) (data not shown), which revealed that this strain may contain only one cry2 gene.…”
Section: Discussionmentioning
confidence: 99%
“…These larvae used in this study were reared in our lab. The bioactivity assay against Pieris rapae Linnaeus, 1758 was performed as described by Song et al (22). The first-instar larvae were placed into 100 ml dechlorinated water.…”
Section: Evaluation Of Insecticidal Activitymentioning
confidence: 99%
“…Larvae susceptibility of P. xylostella (second instar) and L. decemlineata (second instar) was tested using the leaf dip method with some modification (Tabashnik et al 1993;Song et al 2003). The leaves from cabbage and potato used for bioassay against P. xylostella and L. decemlineata respectively, were first cut to appropriate sizes (the diameter was approximately 10 cm) suitable for putting into the bioassay bottle and washed thoroughly with distilled water containing 0AE005% Triton X-100, and then dried.…”
Section: Bioassaymentioning
confidence: 99%
“…d-endotoxins are of great interest for development of new bioinsecticides and in the control of agriculturally important insect pests. Strains containing novel cry1I genes have been evaluated as a source of new proteins with a broad host range [3,4]. Cry1I proteins were initially characterized by their dual activity towards Lepidoptera and Coleoptera [5].…”
Section: Introductionmentioning
confidence: 99%